Tahukah Anda? Komik Biologi Berbasis Weblog dapat Meningkatkan Motivasi Belajar Siswa SMA - Asham Bin Jamaluddin; Andi Citra Pratiwi (Universitas Negeri Makassar, 2022)
The research is the development of research or Research and Development (R & D). Development models used in this research is the development model of ASSURE development model. This model consists of 6 stages of activities, namely: 1) learner characteristic analysis, 2) state objectives, 3) select, modify or design materials, 4 ) utilize technology, media, and materials, 5) require learner response, and 6) evaluate. The purpose of this research is to produce a valid, practical and effective weblog based learning media for biology comics and increase the motivation of high school students to learn. The assessment instruments consist of three, namely: a) Evaluation of the validity of weblog-based comics biology learning media, b) Practicality in the form of teacher response instruments and student responses to weblog-based biology comics learning media and c) Effectiveness in the form of student response instruments to learning motivation. Based on data analysis, the average validity of the media obtained by three validators is 4.25 (valid). The practicality of weblog-based biology comics learning media obtained teacher responses of 4.4 (high) and student responses of 4.2 (high). The effectiveness value of high school students' learning motivation using weblog-based biology comics as measured by normalized n-gain has increased by 0.61 (medium category). Based on the results of the study it can be concluded that the biology-based learning media for weblogs that are developed are valid, practical and effective. Weblog-based comic media is expected to be one of the media used by teachers, students and schools in the world of learning biology